Reducing the Risk of Groundwater Contamination by Improving Pesticide Storage & Handling - Hickman, John S.; Herbel, Kevin L.; Rogers, Danny H.; Powell, Morgan (My University, 1998)
Five areas of pesticide management on your farmstead should be reviewed: 1) pesticide storage practices; 2) mixing and loading practices; 3) spill cleanup; 4) container disposal practices; and 5) other management practices. When handling pesticides, wear proper protective clothing at all times. Personal protection is not addressed in Farm•A•Syst, because its focus is groundwater and drinking water protection. For more information on personal protection when handling pesticides, contact your county Extension office, Extension Agricultural Engineering, or the Pesticide Use Section, Kansas State Board of Agriculture (see Contacts and References).
EP34_1998-08
Keywords: EP34; Environment and Natural Resources; Health and Safety; EP